2015
DOI: 10.1590/1807-1929/agriambi.v19n9p877-881
|View full text |Cite
|
Sign up to set email alerts
|

Monochromatic light-emitting diode (LED) source in layers hens during the second production cycle

Abstract: Light is an important environmental factor for birds, allowing not only their vision, but also influencing their physiological responses, such as behavioral and reproductive activity. The objective of this experiment was to evaluate the impact of different colors of monochromatic light (LED) sources in laying hens production during the second laying cycle. The study was conducted in an experimental laying house during 70 days. A total of 300 laying hens Isa Brown® genetic strain, aged 95 weeks, in the second l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Lighting is one of the essential environmental factors in confined poultry houses. Light not only provides illumination for the poultry but also influences their physiological responses, behavior, growth and development, and production performance ( Lewis and Morris, 1998 ; Olanrewaju et al., 2006 ; Parvin et al., 2014 ; Borille et al., 2015 ). Currently, owing to the high energy efficiency, long working life, availability in different peak wavelengths, low electricity consumption, and low rearing cost ( Hassan et al., 2013 , 2014 ; Huber-Eicher et al., 2013 ; Sultana et al., 2013a , b ; Liu et al., 2017 ), light-emitting diodes ( LED ) are gradually becoming a substitute for conventional incandescent and fluorescent lights for lighting in poultry houses ( Yang et al., 2016 ; Li et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lighting is one of the essential environmental factors in confined poultry houses. Light not only provides illumination for the poultry but also influences their physiological responses, behavior, growth and development, and production performance ( Lewis and Morris, 1998 ; Olanrewaju et al., 2006 ; Parvin et al., 2014 ; Borille et al., 2015 ). Currently, owing to the high energy efficiency, long working life, availability in different peak wavelengths, low electricity consumption, and low rearing cost ( Hassan et al., 2013 , 2014 ; Huber-Eicher et al., 2013 ; Sultana et al., 2013a , b ; Liu et al., 2017 ), light-emitting diodes ( LED ) are gradually becoming a substitute for conventional incandescent and fluorescent lights for lighting in poultry houses ( Yang et al., 2016 ; Li et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Light can be detected by the eye photoreceptor, pineal glands, and hypothalamus so that it causes ovarian activity, sexual maturity, and egg production. Photoperiod is very essential in controlling the poultry's growth, sexual maturity, and reproductive performance, health, and behavior (Baxter et al, 2014;Borille et al, 2015). This research was designed to study the efficacy of curcumin supplementation and the role of monochromatic light in reducing the liver damages during laying period in Magelang ducks.…”
Section: Introductionmentioning
confidence: 99%
“…Use of white or red LEDs did not cause any negative effect on egg production of laying hens (Borille et al, 2013). Borille et al (2015) demonstrated that the use of different colors of LED light in the rearing environment of laying hens in the second cycle did not affect egg production and quality.…”
Section: Introductionmentioning
confidence: 89%